Analysis of Mathematical Concepts in Cowongan Rituals: An Ethnomathematics Study of the Soka Village Community in Batang Regency - Uyuni Aryaningtyas; Widya Safitri; Nur Fadhillah Amelia; Rohmatul Aulia; Siti Fatimah (Ar-Riyadhiyyat: Journal of Mathematics Education, 2026)
This study is an ethnomathematical analysis that focuses on the mathematical concepts embedded in the Cowongan Ritual, an agrarian tradition of the Javanese community that is still preserved in Soka Village, Batang Regency. This ritual is typically performed as a plea for rain during prolonged droughts and represents local wisdom passed down through generations. The research employs a qualitative-descriptive method with an ethnographic approach to understand the symbolic meanings and cultural context of the ritual. Data were collected through observations of all stages of the ritual, in-depth interviews with community members, and documentation. Data analysis focused on identifying mathematical concepts that appear in the symbols, structures, and ritual actions. The main findings identify three formal mathematical concepts that are intuitively applied in this cultural practice: first, the concept of odd numbers, which appears in determining the number of offerings and the repetition of movements, which mathematically reflects an arithmetic sequence with the nth term formula Un​=2n−1; second, modular arithmetic, which underlies the determination of the ritual time on the night of Friday Kliwon, where the 35-day repeating cycle (selapanan) can be modeled as a solution of simultaneous congruences between modulo 7 (day cycle) and modulo 5 (Javanese market-day cycle); and third, symmetry and geometry, which are evident in the circular formation of the procession and the swinging movements of Nini Cowong that contain rotational symmetry, while the ornaments of the effigy also display reflective symmetry. The conclusion of this study is that the Cowongan Ritual contains a strong mathematical structure that is closely integrated with Javanese spiritual and cosmological values, thus making a tangible contribution to the development of contextual mathematics learning based on local culture.